Navigating the fungal battlefield: cysteine-rich antifungal proteins and peptides from Eurotiales - Holzknecht, Jeanett; Marx, Florentine (Frontiers in Fungal Biology, 2024)
Fungi are ubiquitous in the environment and play a key role in the decomposition and recycling of nutrients. On the one hand, their special properties are a great asset for the agricultural and industrial sector, as they are used as source of nutrients, producers of enzymes, pigments, flavorings, and biocontrol agents, and in food processing, bio-remediation and plant growth promotion. On the other hand, they pose a serious challenge to our lives and the environment, as they are responsible for fungal infections in plants, animals and humans. Although host immunity opposes invading pathogens, certain factors favor the manifestation of fungal diseases. The prevalence of fungal infections is on the rise, and there is an alarming increase in the resistance of fungal pathogens to approved drugs. The limited number of antimycotics, the obstacles encountered in the development of new drugs due to the poor tolerability of antifungal agents in patients, the limited number of unique antifungal targets, and the low species specificity contribute to the gradual depletion of the antifungal pipeline and newly discovered antifungal drugs are rare. Promising candidates as next-generation therapeutics are antimicrobial proteins and peptides (AMPs) produced by numerous prokaryotic and eukaryotic organisms belonging to all kingdom classes. Importantly, filamentous fungi from the order Eurotiales have been shown to be a rich source of AMPs with specific antifungal activity. A growing number of published studies reflects the efforts made in the search for new antifungal proteins and peptides (AFPs), their efficacy, species specificity and applicability. In this review, we discuss important aspects related to fungi, their impact on our life and issues involved in treating fungal infections in plants, animals and humans. We specifically highlight the potential of AFPs from Eurotiales as promising alternative antifungal therapeutics. This article provides insight into the structural features, mode of action, and progress made towards their potential application in a clinical and agricultural setting. It also identifies the challenges that must be overcome in order to develop AFPs into therapeutics.